Effectiveness of non-pharmacological intervention protocol for prevention of postoperative delirium in the surgical intensive care unit - Thassayu Yuyen; Akarawat Narksut; Suchanun Lao-amornphunkul; Chayanan Thanakiattiwibun; Cholticha Pansangar; Napat Thikom; Onuma Chaiwat; Annop Piriyapatsom (Scientific Reports)
Abstract Postoperative delirium (POD) is a common adverse event in patients admitted to the intensive care unit (ICU). We aimed to determine the effectiveness of a multicomponent non-pharmacological intervention protocol to reduce the incidence of POD in elderly patients admitted to the surgical ICU (SICU). This before-and-after cohort study included 300 patients aged ≥ 65 years who were admitted to the SICU within 7 days postoperatively with an anticipated SICU stay > 24 h. During the pre-intervention period, patients received medical care based on the attending physicians. While during the intervention, patients received the same medical care plus a multicomponent non-pharmacological intervention protocol. POD was monitored twice daily using the Confusion Assessment Method for the ICU. Demographic and clinical data during SICU stay were collected and compared between the pre-intervention and intervention periods. The primary outcome was POD incidence. The secondary outcomes were POD duration, delirium-free days, and other clinical outcomes. The incidences of POD during the pre-intervention and intervention periods were not different (40.0% vs. 38.0%, P = 0.723; OR 0.92, 95% CI 0.58–1.46). Multivariate regression analyses with two different models demonstrated that the multicomponent non-pharmacological intervention protocol was not associated with POD prevention (OR 0.70, 95% CI 0.39–1.25 for Model 1 and OR 0.63, 95% CI 0.37–1.08 for Model 2). The protocol was associated with lower incidence of SICU events, particularly self-removal of endotracheal tube and nosocomial infection. Implementation of the multicomponent non-pharmacological intervention protocol was not associated with POD prevention in elderly patients admitted to the SICU. Trial registration Thai Clinical Trials Registry. Trial No. TCTR20181201001. Retrospective registered 01 December 2018.